PEMANFAATAN LARGE LANGUAGE MODEL (LLM) SEBAGAI ASISTEN PEMBELAJARAN DIGITAL DALAM MENINGKATKAN EFEKTIVITAS PROSES BELAJAR MAHASISWA - Sharon Jadelyn Villian Johan; Mayang Sari Nr; Anita Anita; Dorie P. Kesuma (Jurnal Riset Teknik Komputer, 2026)
The development of Artificial Intelligence (AI) technology has significantly impacted various sectors, including education. One of the most rapidly advancing innovations is the Large Language Model (LLM), an AI-based language model capable of understanding and generating natural language text. This study aims to examine how Large Language Models can be utilized as digital learning assistants to support the teaching and learning process. The research method employed is a literature review by reading and analyzing various scientific journals, books, research reports, and relevant academic publications from the last five years. The analysis was conducted to identify the benefits, opportunities, challenges, and implications of using Large Language Models in the field of education. The findings indicate that Large Language Models can assist students in understanding learning materials, obtaining information quickly, supporting self-directed learning, and enhancing interaction in the learning process. On the other hand, the use of Large Language Models also presents several challenges, such as information accuracy, potential user dependency, and academic ethics issues. Based on the findings, Large Language Models have significant potential as digital learning assistants that can improve learning effectiveness when used wisely and supported by adequate digital literacy.